2008
DOI: 10.1111/j.1743-6109.2008.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Serum Sex Hormones, Erectile Function, and Sex Drive: The Olmsted County Study of Urinary Symptoms and Health Status Among Men

Abstract: Few studies have examined the association between sex hormone serum levels, erectile function, and sex drive. Using data from the Olmsted County Study of Urinary Symptoms and Health Status among Men we examined the associations between sex hormone serum levels, erectile function, and sex drive. During 1989-1991, Caucasian men ages 40-79 years were randomly selected from Olmsted County, MN, and in the sixth year of follow-up questions on sexual function from the Brief Male Sexual Function Inventory were added a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 43 publications
5
26
1
1
Order By: Relevance
“…The ages of the men in these studies ranged from 26 to 83 years of age, and higher rates were seen in older cohorts; for instance, 66 cases per 1,000 person‐years were observed in the Brazilian Men's Health Study (age range 60–83 years [26]). Lower incidence rates were also observed in studies that used only two questions to assess ED [27].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The ages of the men in these studies ranged from 26 to 83 years of age, and higher rates were seen in older cohorts; for instance, 66 cases per 1,000 person‐years were observed in the Brazilian Men's Health Study (age range 60–83 years [26]). Lower incidence rates were also observed in studies that used only two questions to assess ED [27].…”
Section: Discussionmentioning
confidence: 75%
“…By contrast, low solitary and dyadic desire remitted in 21.8% and 15.3% of men, respectively. Previous prospective studies [24,27] have also found that sexual desire was relatively well preserved into old age, although these studies did not distinguish between dyadic and solitary desire (the MMAS did, however, report a decreased masturbatory frequency in older men). Data from the present study concur with our previous cross‐sectional observations [15] and others [13], showing a marked preference for partnering that is maintained well into older age.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A longitudinal study also showed a close relationship between the serum testosterone level and sexual desire 27. The Olmsted County Study, with its large number of subjects, showed an association between a higher testosterone level and an increase in sexual desire 28. When reduced sexual desire is primarily due to hypogonadism, two meta-analyses of RCTs demonstrated a significant improvement in sexual desire after TRT 25,26.…”
Section: Sexual Dysfunctionmentioning
confidence: 97%
“…Testosterone is widely accepted as playing a role in male sexual anatomy and function [15, 16]. However, its physiological role in human erectile function remains a matter of some controversy [1720].…”
Section: Role Of Testosterone In Cellular Physiology: John Mulhall Kmentioning
confidence: 99%